Cost-effective synthesis of copper sulfide nanoparticles and flexible films for photocatalytic and antibiotic applications - Jung, Jina; Jeon, Hye Jin; Yang, Sung Woong; Choi, Myeong geun; Vidyasagar, Devthade; Kim, Jeong Hyeok; Shim, Ryun Bo; Yun, Yeonghun; Han, Sehoon; Cho, In Sun; Han, Jee Eun; Lee, Sangwook (Journal of Materials Research and Technology, 2024)
Herein, we investigate the effects of temperature and thiourea addition rate on the synthesis of copper sulfide nanoparticles (CuS NPs) via a chemical co-precipitation method, exploring their impact on the size and morphology of CuS NPs. Our systematic approach resulted in the successful synthesis of CuS NPs with significantly smaller nanoflower sizes than previously reported in the literature, providing insights into the nucleation and growth mechanisms under various synthesis conditions. Furthermore, the photocatalytic activity of the synthesized CuS NPs with three types of distinctive morphologies, namely, nanoflowers with 50 nm diameter (F-50), nanoflowers with 200 nm diameter, and nanogravels with 50 nm diameter, is comparatively analyzed. Notably, the F-50 exhibits a superior photocatalytic performance compared to the other samples, demonstrating the considerable influence of the NP size and morphology on their functional properties. Furthermore, the antibacterial property of the small CuS nanoflowers is examined using an antibacterial film fabricated by coating the NPs on a polyethylene terephthalate substrate, which is widely used as a protective or packaging film in various industries because of its transparency and flexibility. The antibacterial film can be used to kill both gram-positive and -negative bacteria effectively. This research contributes significantly to the understanding and optimization of CuS NP synthesis and application, emphasizing the potential of small-sized nanoflower CuS NPs in photocatalysis and antibacterial applications.
Keywords: Addition rate; Antibacterial films; Antibiotic film; Cost effective; Effective synthesis; Effects of temperature; Flexible films; Nanoparticle films; Photo-catalytic; Scalable synthesis; Antibiotic film; Copper sulfide; Nanoflowers; Photocatalyst; Scalable synthesis